Teacher's Recast and Corrective Feedback In Classroom Interaction - Kurniawati Buchari (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
The purpose of this study was to find out the use of recast as corrective feedback in classroom interaction. This study examined the most common corrective feedback teachers use in classroom interactions, and why teachers use corrective feedback in classroom interactions. The research used qualitative methods and it used observation sheets and audio recorders. The writer collected data through observations to generate the main data and through interviews to support the primary data. In addition, for audio recorder, the writer listened carefully, played it part by part and make it into a script then analyzed and elaborated it. The sample for this study consisted of 34 students whose English skill were in basic and two English teachers who have been teaching English for more than three years.  Data were analyzed by a qualitative procedure based on the Mile and Huberman (2013) model. This includes data reduction through analyzing the core part that consisted of corrective feedback, data display, and inference. Results showed that the most common corrective feedback used by teachers in classroom interactions was recast, it occurred about 66.7% or 64 times in class. The survey turned out to be corrective feedback from the teacher either recast or other corrective feedback types. Interviews revealed that there were three reasons for using corrective feedback by the teacher, namely to help students avoid mistakes; to improve students' grammar, vocabulary, and pronunciation; and to motivate students to learn languages. Those reasons also supported the previous theory or research which conducted by some researchers.